Percutaneous edge-to-edge repair for systemic tricuspid valve regurgitation in patients with congenital heart disease: the first descriptive cohort. (3rd October 2022) - Guerin, P; Jalal, Z; Cueff, C; Hascoet, S; Bouvaist, H; Levy, F; Hugues, N; Ladouceur, M; Malekzadeh-Milani, S G; Iriart, X; Silini, A; Karam, N; et al.
Abstract: : In patients with congenital heart diseases (CHD) systemic tricuspid regurgitation (STR) is frequent. Here, we report our experience with percutaneous edge-to-edge repair (PETER) in a series of 12 CHD patients with STR using the MitraClip system. Twelve patients (median age = 35 years, 83% males) with severe STR (ccTGA (n=5), asTGA (n=3), SV (n=4)), at high-risk for surgical treatment, gave informed consent for treatment using PETER. The XTR MitraClip device (Abbott, Santa Clara, CA) was used. At baseline, 7/12 patients were in NYHA functional class ≥ III. Standard femoral venous access was successfully used in 10/12 patients. In SV patients, the systemic valve was accessed directly through the right atrium (n=2), after a Fontan conduit puncture (n=1), or after direct atrial surgical access (n=1). In TGA patients, either transseptal (ccTGA patients, n=4) or transbaffle (asTGA patients, n=3) puncture was performed (4). Mitraclip devices were successfully implanted in 11/12 patients (Figure 1). One procedural complication was reported for a patient with SV in whom a septal leaflet rupture occurred following clip release, leading to severe STR; the patient died from refractory cardiac failure one week later. Peri-procedural complications included one case of left femoral vein injury and one case of atrial flutter treated by catheter ablation. After a median follow-up of 12-months (range 1–25) following device implantation, no death had occurred. The patients had significant reduction in STR (from severe to moderate in 10/11 patients) and clinically improved (10/11 patients were in NYHA class I or II). To conclude, percutaneous edge-to-edge therapy of STR in CHD patients is feasible, safe and effective to reduce STR and SRV dilatation. This reduction is associated with a significant clinical improvement. Funding Acknowledgement: Type of funding sources: None.